Effect of Integrated Lecture‐, Case‐, and Problem‐Based Learning on Critical Thinking and Clinical Competence in Gastrointestinal Surgery Trainees: A Randomized Controlled Trial. - Tang, Jin; Yang, Jing; Yang, Junsong; Wei, Shoujiang; Lindberg, Greger (Gastroenterology Research & Practice, 2026)
Background: Enhancing clinical thinking and competence is central to gastrointestinal surgical training. This study is aimed at evaluating the effectiveness of an integrated instructional model combining lecture‐based learning (LBL), problem‐based learning (PBL), and case‐based learning (CBL) in gastrointestinal surgical training. Methods: This prospective randomized controlled trial was conducted at the Affiliated Hospital of North Sichuan Medical College, China, from September to November 2024. A total of 120 gastrointestinal surgical trainees, including final‐year medical interns and first‐year surgical residents, were randomly assigned (1:1:1) to the LBL, PBL + CBL, or integrated LBL + PBL + CBL groups using a computer‐generated sequence, with allocation concealed by an independent assistant. After completing an 8‐week standardized curriculum delivered by the same teaching team, the following outcomes were assessed: critical thinking ability using the Chinese version of the California critical thinking disposition inventory (CTDI‐CV); theoretical knowledge through written and oral examinations; learning efficiency (study time and task completion rate) and satisfaction; and clinical competence assessed via the miniclinical evaluation exercise (Mini‐CEX). Data were analyzed using IBM SPSS Statistics with one‐way analysis of variance, and statistical significance was set at p < 0.05. Results: The integrated LBL + PBL + CBL groups achieved the highest CTDI‐CV total scores, theoretical knowledge performance, and Mini‐CEX scores compared with the other groups (p < 0.05). Despite reporting the shortest weekly study time, the integrated group attained the highest task completion rate and learner satisfaction score (p < 0.05). Conclusion: The integrated LBL + PBL + CBL approach enhances efficiency and is well‐suited for advancing clinical competence in surgical training. Trial registration: Chinese Clinical Trial Registry (ChiCTR2000041569).